2013
DOI: 10.1063/1.4789394
|View full text |Cite
|
Sign up to set email alerts
|

Strong interfacial dipole formation with thermal evaporation of lithium cobalt oxide for efficient electron injections

Abstract: We investigated the electronic structures at the interface of Al/lithium cobalt oxide (LiCoO2)/tris(8-hydoxyquinoline) aluminum (Alq3) to elucidate the origin of the electron injection enhancement with the insertion of the LiCoO2 layer in organic light-emitting devices using in situ photoelectron spectroscopy experiments. We discovered that LiCoO2 was decomposed into lithium oxide (Li2O) by thermal evaporation, and only Li2O was deposited on the desired substrate. Li2O forms a strong interfacial dipole, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[20,21] It is reported that the electron injection barrier in an OLED device can be dramatically decreased by an Li 2 O layer due to the strong dipole formation in the interface layer. [22] We speculate that the dipole formation also happens in our PSC in the thin Li 2 CO 3 layer. It lowers the work-function of the ITO cathode and thus explains the enhancement of 𝑉 oc in our experiment (Fig.…”
mentioning
confidence: 61%
“…[20,21] It is reported that the electron injection barrier in an OLED device can be dramatically decreased by an Li 2 O layer due to the strong dipole formation in the interface layer. [22] We speculate that the dipole formation also happens in our PSC in the thin Li 2 CO 3 layer. It lowers the work-function of the ITO cathode and thus explains the enhancement of 𝑉 oc in our experiment (Fig.…”
mentioning
confidence: 61%
“…[1,2] The inkjet printing technology has demonstrated a great potential of application in the all-printed electronic industry due to its features of high efficiency, low-cost, low waste, and noncontact process. [3,4] Compared with the traditional thin layer deposition techniques, such as photolithography, [5,6] electrochemical deposition, [7,8] and thermal evaporation, [9,10] inkjet printing has better compatibility with various materials. [11,12] Polymer, metal, semiconductor, and ceramics solutions can be printed on the solid or flexible substrate by inkjet printing, which provides to be a decent way to fabricate all-printed electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Such interfacial electronic structures can be studied thoroughly with photoemission spectroscopy (PES) during in situ interface formation. Although the energy level alignment between the electrode and the active organic material has been successfully investigated, [27][28][29] the study of the OSC interface has encountered a critical obstacle, as mentioned above; the polymer active layer cannot be deposited in a stepwise manner in situ; this hinders the ability to analyze the initial interface formation. Recently, our group developed an electrospray deposition technique, which can directly deposit polymers on a substrate in a vacuum chamber with nanometer thickness control.…”
mentioning
confidence: 99%